Oxidative Stress and Its Consequences in the Blood of Rats Irradiated with UV: Protective Effect of Cannabidiol - Michał Biernacki; Małgorzata Michalina Brzóska; Agnieszka Markowska; Małgorzata Gałażyn-Sidorczuk; Bogdan Cylwik; Agnieszka Gęgotek; Elżbieta Skrzydlewska (MDPI AG, 2021)
UVA/UVB radiation disturbs the redox balance of skin cells, and metabolic consequences can be transferred into the blood and internal tissues, especially after chronic skin exposure to UV radiation. Therefore, the aim of this study was to evaluate the effect of cannabidiol (CBD), an antioxidant and anti-inflammatory phytocannabinoid, on oxidative stress and its consequences in the blood of nude rats whose skin was exposed to UVA/UVB radiation for 4 weeks. It was shown that CBD penetrated the blood and in UVB-irradiated rats was preferentially located in the membranes of polymorphonuclear leukocytes, which promoted reduction of ROS generation and up-regulation of antioxidant ability by increasing the activity of glutathione reductase and thioredoxin reductase, while the level of reduced glutathione decreased by UV radiation. Consequently, reduction in UV-induced lipid peroxidation, assessed as 4-hydroxynonenal (4-HNE) and 8-isoprostane (8-isoPGF2α) as well as protein modifications, estimated as 4-HNE-protein adducts and protein carbonyl groups, was observed. CBD, by countering the UV-induced down-regulation of 2-arachidonylglycerol, promoted its antioxidant/anti-inflammatory effects by reducing CB1 and increasing PPARγ receptor activation and consequently ROS and TNF-α down-regulation. The results suggest that CBD applied topically to the skin minimizes redox changes not only at the skin level, but also at the systemic level.